Targeting the androgen receptor (AR) with AR degradation enhancer ASC-J9® led to increase docetaxel sensitivity via suppressing the p21 expression. (1st March 2019) - Luo, Jie; Tian, Jing; Chou, FuJu; Lin, Changyi; Xing, Emily Zixin; Zuo, Li; Niu, Yuanjie; Yeh, Shuyuan; Chang, Chawnshang
Abstract: Chemotherapy with docetaxel remains the effective therapy to suppress castration resistant prostate cancer (CRPC) in some patients. However, most chemotherapy with docetaxel eventually fails with the development of docetaxel resistance after 18-weeks of treatment. Here we found docetaxel treatment might have an adverse effect of increasing the androgen receptor (AR) protein level in the CRPC cells, and combining docetaxel with anti-AR therapy using AR-shRNA or the AR degradation enhancer ASC-J9® may increase docetaxel sensitivity to better suppress the CRPC cell growth. Mechanism dissection found docetaxel might have the adverse effect of increasing the AR protein stability via suppressing the AR ubiquitination due to the increased AR phosphorylation. The consequence of such increased AR protein may then lead to increase p21 expression via transcriptional regulation. Preclinical studies with in vitro cells lines also demonstrated that targeting AR with ASC-J9® led to suppressing the AR-increased p21 expression to improve the docetaxel sensitivity in the CRPC cells that already developed docetaxel resistance. Together, these results suggest that a combined therapy of docetaxel and ASC-J9® is a novel therapy to better suppress CRPC in patients that already developed docetaxel resistance. Highlights: Docetaxel can increase AR expression in prostate cancer. Docetaxel promotes CDK-dependent AR phosphorylation to enhance AR protein stability. The high level of AR expression can inhibit the docetaxel sensitivity via inducing p21. Targeting AR by ASC-J9 can increase docetaxel sensitivity and reduce the docetaxel resistance in PCa cells.